2007
DOI: 10.1007/s11340-006-9013-9
|View full text |Cite
|
Sign up to set email alerts
|

Cure-dependent Viscoelastic Poisson’s Ratio of Epoxy

Abstract: The evolution of the lateral contraction ratio of two commercial (high and low temperature cure) epoxy resins is studied in uniaxial tension using moiré interferometry. The ratio of transverse to axial strains evolves from an elastic value of about 0.40 to a rubbery plateau value of 0.49 at long times. Furthermore, the data indicate that the contraction ratio follows timetemperature superposition with a shift function indistinguishable from other axial viscoelastic functions. The lateral contraction behavior a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 29 publications
6
41
0
1
Order By: Relevance
“…Finally, the data obtained from the Poisson's ratio measured in CDR experiments, shows an intermediate behavior, exhibiting values close to those measured for the moduli functions for temperature up to 40°C, while a deviation is exhibited for higher temperatures, with a slope similar to that shown by the # REL set of data. Previous literature data have always shown that the shift factors required for the Poisson's ratio master curve construction are the same as those obtained for other viscoelastic functions [10,17,20]. The difference found between master curves distribution and between the related shift factors are effects not fully understood, and that could be tentatively ascribed to an interference due to the contact extensometer.…”
Section: Constant Deformation Testsmentioning
confidence: 69%
See 3 more Smart Citations
“…Finally, the data obtained from the Poisson's ratio measured in CDR experiments, shows an intermediate behavior, exhibiting values close to those measured for the moduli functions for temperature up to 40°C, while a deviation is exhibited for higher temperatures, with a slope similar to that shown by the # REL set of data. Previous literature data have always shown that the shift factors required for the Poisson's ratio master curve construction are the same as those obtained for other viscoelastic functions [10,17,20]. The difference found between master curves distribution and between the related shift factors are effects not fully understood, and that could be tentatively ascribed to an interference due to the contact extensometer.…”
Section: Constant Deformation Testsmentioning
confidence: 69%
“…Not being directly in possession of data regarding the effect of temperature on relaxation Poisson's ratio of amorphous materials, our results were compared with literature data, which underline some relevant differences between semicrystalline and amorphous polymers. O'Brien et al [17] reported isothermal curves of the viscoelastic so-called lateral contraction ratio for epoxy resins under creep conditions. They evidenced an upper plateau at 0.49 for temperatures approaching the glass transition region, while the simultaneously measured creep compliance still displays an increasing trend.…”
Section: Constant Deformation Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work by White and coworkers indicates that the timetemperature superposition shift factors for the bulk and axial responses are identical, based on measurements of the time-dependent Poisson's ratio during uniaxial elongation. 11 Bero and Plazek 12 also found that the bulk and shear retardation functions were identical (after a vertical shift) at short times although the shear response included longer time mechanisms not present in the bulk response. We note that Bero and Plazek measured the volumetric response to small temperature jumps in the glass transition region and from time-temperature superposition obtained a reduced curve that was related to the time-dependent bulk compliance; the need for small temperature jumps to ensure linearity of the volume recovery experiments was articulated.…”
Section: Introductionmentioning
confidence: 93%